Effects of cooling on human skin and skeletal muscle - Yanagisawa, O.; Homma, T.; Okuwaki, T.; Shimao, D.; Takahashi, H. (European Journal of Applied Physiology, 2007)
To investigate the effects of cooling on local temperature and circulation in the skin and skeletal muscle at different cooling temperatures. Ten male subjects (mean age 24.9 years) participated in this study. Intramuscular temperatures were measured by inserting two 22-gauge temperature probes (needle length; 8 and 18 mm) into the ankle dorsiflexors, while skin temperature was measured using a thermocouple attached to the leg skin anteriorly. Near-infrared spectroscopy was also used to evaluate the concentration changes in oxygenated, deoxygenated, and total hemoglobin/myoglobin in local skin and skeletal muscle. These measurements were simultaneously performed during the 10-min noncooling, 30-min cooling (cooling pad temperature; 0, 10, or 20°C), and 60-min recovery periods. Under all cooling conditions, skin and intramuscular temperatures decreased during cooling (P < 0.01) and began to increase after the cooling pad was removed. However, these values did not return to baseline values during the recovery period (P < 0.01). Moreover, tissue temperatures tended to show lower values during cooling at lower cooling temperatures. All hemoglobin/myoglobin concentrations also showed a concomitant significant decrease during cooling under three cooling conditions (P < 0.01); the oxygenated and total hemoglobin/myoglobin concentrations did not return to the exact values before cooling during the recovery period. This study suggested that the rate of decrease in tissue temperature depends on the cooling temperature and the effects of cooling on tissue temperatures and circulation tend to be maintained during 60 min post-cooling period despite the cooling temperature.